Recent Advances in Corneal Collagen Crosslinking in thin Corneas - Deepa Gupta; Ritika Sachdev; Mahipal Sachdev (Delhi Journal of Ophthalmology)
Corneal collagen crosslinking has been a breakthrough in keratoconus management since its inception as it offers stabilization of the progressive ectasia. However, the limitation of its use in thin corneas (< 400 microns) is a limiting factor and various methods have been devised to overcome this shortcoming. Modifications like application of hyposmolar riboflavin, transepithelial collagen cross-linking (CXL) and customized epithelial debridement have been tried but have limited clinical data. Contact lens assisted and SMILE lenticule assisted CXL are new entrants for application on the thin corneas. The article highlights the various modifications employed in tackling thin corneas in CXL.